Comparing the Effectiveness of Mentalization-Based Therapy and Dialectical Behavior Therapy on Time Perception and Self-Forgiveness in Adolescents with Self-Injurious Behaviors - Mehrmanesh, Mehri; Zarghami, Elham; Nasrolahi, Bita (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to determine the differences in the effectiveness of Mentalization-Based Therapy and Dialectical Behavior Therapy on time perception and self-forgiveness in adolescents with self-injurious behaviors. Methods and Materials: This applied study employed a quasi-experimental design with a pretest–posttest control group and a two-month follow-up. The statistical population consisted of adolescent girls aged 13–18 years with self-injurious behaviors who were referred to counseling centers in Tehran during the second half of 1403. A total of 45 participants were selected through purposive sampling and randomly assigned into two experimental groups (Mentalization-Based Therapy and Dialectical Behavior Therapy) and one control group (15 participants per group). The experimental groups received 12 sessions of their respective interventions, while the control group remained on a waiting list. Data were collected using the Self-Forgiveness Scale and the Adolescent Time Perspective Questionnaire. Data analysis was conducted using SPSS-26 at both descriptive and inferential levels, including multivariate analysis of variance, repeated measures ANOVA, and Bonferroni post hoc tests, after verifying statistical assumptions. Findings: The results of repeated measures ANOVA indicated significant main effects of time and group, as well as significant interaction effects between time and group for positive time perception, negative time perception, and self-forgiveness (p < 0.001). Bonferroni post hoc tests revealed that both experimental groups showed significant improvements compared to the control group at posttest and follow-up (p < 0.05). Specifically, positive time perception and self-forgiveness increased significantly, while negative time perception decreased significantly in both intervention groups. Furthermore, the Mentalization-Based Therapy group demonstrated significantly greater improvements than the Dialectical Behavior Therapy group in most variables, particularly at follow-up (p < 0.05), indicating stronger and more sustained effects. Conclusion: The findings suggest that both Mentalization-Based Therapy and Dialectical Behavior Therapy are effective interventions for improving time perception and self-forgiveness and reducing maladaptive cognitive-emotional patterns in adolescents with self-injurious behaviors; however, Mentalization-Based Therapy appears to have relatively greater and more enduring effects, highlighting its potential as a preferred intervention in this population.